Analisis Kedalaman Pemotongan Terhadap Distribusi Gaya Pemotongan Pada Bed Mesin Bubut - Risa Bernadip Umar; Ramli (Fakultas Teknik UPRI, 2024)
This study aims to determine the magnitude of cutting forces, describe and identify the reactionforces on the base (bed) of a lathe machine, and to find the relationship between depth of cut andthe reaction forces on the machine bed resulting from the distribution of cutting forces during theturning process. The experiment was carried out by turning a concrete iron rod (low carbon steel)with a diameter of 25 mm. The turning process was conducted by varying the depth of cut from0.125 mm to 0.625 mm (with 0.125 mm intervals), spindle speeds of 85, 180, 540, and 800 rpm, andfeed rates of 0.1 mm/rev and 0.2 mm/rev. The analysis of the cutting force distribution on themachine bed resulted in the identification of reaction forces and torque moments.The results showthat an increase in cutting depth leads to an increase in cutting force, which in turn increases thereaction forces and torque moments on the bed of the machine due to the distribution of cuttingforces. The components of the cutting force are as follows: tangential force = 72–81%, longitudinal(axial) force = 55–60%, and radial force = 27–31% of the total cutting force.The reaction forcesacting on the machine bed include forces distributed along the bed, which are equivalent to thelongitudinal (axial) force component, and downward forces acting on the middle part of the bed.Torque moments occur at both ends of the bed, specifically under the headstock and tailstock (inthe clockwise direction). The final results indicate that torque moments have the most significantimpact on the structural safety of the machine bed. The magnitude of the reaction force at the center